2021
DOI: 10.3390/healthcare9060642
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mindfulness-Based Mandala Coloring, Made in Nature, on Chronic Widespread Musculoskeletal Pain: Randomized Trial

Abstract: This study aimed to investigate the effects of mindfulness-based mandala coloring made within nature on individuals with chronic widespread musculoskeletal pain (CWP). Thirty-six participants were randomly allocated. In the experimental group, identical interventions and procedures were administered for each experiment. The control group members were untreated and remained in an urban environment. Overall, the experiment showed significant improvements in tender points (f = 8.791, p = 0.006), total stress leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Among the eligible studies in this review, intervention durations ranged from 15 min to 8 weeks, with 1 to 12 sessions in total. In addition, each session duration differed from 15 min to 4 h. In two studies, the intervention group receives the cointervention: meditation techniques 18 and mindfulness-based intervention, 20 respectively. Only two studies included software-based intervention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the eligible studies in this review, intervention durations ranged from 15 min to 8 weeks, with 1 to 12 sessions in total. In addition, each session duration differed from 15 min to 4 h. In two studies, the intervention group receives the cointervention: meditation techniques 18 and mindfulness-based intervention, 20 respectively. Only two studies included software-based intervention.…”
Section: Resultsmentioning
confidence: 99%
“… 19 The outcome measures for depression included the Center for Epidemiologic Studies-Depression Scale, 39 and the HADS. 38 The outcome measures for stress included the Stress Response Inventory-Modified Form 20 ; the specific physiological stress response reflected in changes in vital signs 19 , 40 and stress hormone cortisol. 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Moreover, this study has reported similar results that a previous study in which indicated implementing forest therapy and mindfulness-based intervention in nature have increased health-related quality of life 34 and stress level. 35 for patients with chronic widespread pain. In terms of changes in HRV, the result identified a significant increase in heart rate.…”
Section: Inmentioning
confidence: 99%
“…A review of the literature shows that mandala studies in nursing can have a positive effect on pediatric oncology patients (Gurcan & Atay Turan, 2021), coping with university students' anxiety (Carsley & Heath, 2020), and spirituality (Shiah & Hwang, 2019). Mindfulness‐based activities keep one's attention on “the moment,” causing the person to make sense of their experiences, increase their well‐being, and feel more comfortable (Choi et al, 2021). The literature shows that there are reasons to believe that people with high mindfulness can experience spirituality more, thereby increasing their well‐being and comfort (Da Silva & Pereira, 2017; Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%